Arabic As a Medium for the Internalization of Worship Values - Aisa, Aufia; Rahmawati, Rina Dian; Fahmi, Muhammad Fatkhur Rizal; Rohmah, Umi Unzilatur; Septia, Hilza Safa (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study examines the role of Arabic language instruction as a medium for internalizing worship values through the Takhassus Program at MTsN 3 Jombang. The research data comprise Arabic learning activities directly integrated with students’ daily worship routines, such as ablution (wudhu), prayer, dhikr, and the use of Arabic expressions in everyday communication. The data sources include primary data from participant observation and in-depth interviews with 10 seventh-grade students, 2 Arabic teachers, and 1 principal, as well as secondary data such as program documents, lesson plans, and school archives. A qualitative case study design was employed, with purposive sampling to select informants directly involved in the program. Data collection combined participant observation, interviews, and documentation, while data were analyzed using Miles and Huberman’s interactive model: data reduction, display, and conclusion drawing. The findings show that Arabic instruction is functionally embedded in students’ worship practices, positioning the language as both a communicative and devotional tool. This integration is strengthened by teacher modeling and the school’s spiritual climate, supporting the internalization of worship values. The study contributes theoretically by framing Arabic as a value-based pedagogical instrument and practically by offering a contextual, replicable model for Islamic schools. Although challenges exist, such as limited time and difficulties understanding classical texts, these are addressed through extracurricular activities and traditional methods like sorogan and bandongan. Thus, Arabic language instruction linked to worship practice serves as a transformative approach for developing students’ moral and spiritual character in a sustainable way.